THE AGING OF THE POPULATION: SOCIO-ECONOMIC ASPECT - S. Kuzin (Вестник университета, 2018)
The age structure of the population of modern Russia tends to increase the proportion of elderly people aged 60 years and older. Experts in the field of socio-economic and demographic statistics, sociology, gerontology argue that this trend is due to the influence of the following factors: improvement of living conditions; development of medicine; decrease in the birth rate; increase in the number of citizens with low economic activity (aged 60 years and over). A possible solution to the problem of population ageing is the increase in the retirement age. This measure is effective in the long term, but in this case it is necessary to continue to extend the average life expectancy, to strengthen the health of citizens and to create additional institutions to provide employment to persons who are close to retirement age.